2022
DOI: 10.1002/edn3.343
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal monitoring of lake fish spawning activity using environmental DNA metabarcoding

Abstract: Determining the timing and location of fish reproductive events is crucial for the implementation of correct management and conservation schemes. Conventional methods used to monitor these events are often unable to assess the spawning activity directly or can be invasive and therefore problematic. This is especially the case when threatened fish populations are the study subject, such as the Arctic charr (Salvelinus alpinus L.) populations in Windermere (Cumbria, UK). Arctic charr populations have been studie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 101 publications
2
10
0
1
Order By: Relevance
“…Our study is not the only that detected fish spawning events trough metabarcoding. Di Muri et al (2022) observed peaks or Arctic char (Salvelinus alpinus) during spawning seasons at specific locations of known spawning sites as we did in our study for some fish species (i.e., C. lavaretus, P. fluviatilis, T. tinca, and G. aculeauts). Even though the information obtained through metabarcoding is not as accurate as that obtained using species-specific PCR assays, metabarcoding allows to have an overview of the trend of the community composition.…”
Section: Biofilms Edna Enable To Monitor Temporal and Spatial Changes...supporting
confidence: 58%
“…Our study is not the only that detected fish spawning events trough metabarcoding. Di Muri et al (2022) observed peaks or Arctic char (Salvelinus alpinus) during spawning seasons at specific locations of known spawning sites as we did in our study for some fish species (i.e., C. lavaretus, P. fluviatilis, T. tinca, and G. aculeauts). Even though the information obtained through metabarcoding is not as accurate as that obtained using species-specific PCR assays, metabarcoding allows to have an overview of the trend of the community composition.…”
Section: Biofilms Edna Enable To Monitor Temporal and Spatial Changes...supporting
confidence: 58%
“…A second major consideration regarding eDNA natural dynamics for this study is to ensure eDNA samples are taken where eDNA has accumulated within each lake. Accumulation of fish eDNA can occur either through shedding of scales, excrement, gametes, or decaying bodies (Di Muri et al, 2022; Wang et al, 2021). As such, it is important to include sufficient spatial sampling to avoid false negatives when conducting eDNA surveys (Di Muri et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of fish eDNA can occur either through shedding of scales, excrement, gametes, or decaying bodies (Di Muri et al, 2022; Wang et al, 2021). As such, it is important to include sufficient spatial sampling to avoid false negatives when conducting eDNA surveys (Di Muri et al, 2022). Here the spatial distribution of eDNA was found to be randomly distributed with no clear spatial structure within individual lakes.…”
Section: Discussionmentioning
confidence: 99%
“…Di Muri et al (2023) assess the effectiveness of eDNA metabarcoding for inferring the spatiotemporal distribution of the spawning activity of Arctic char ( Salvelinus alpinus ) in Windermere, UK, and observe corresponding peaks of relative read numbers with conventional netting survey. They show that eDNA metabarcoding may accurately and efficiently define the spatial and temporal characteristics of fish spawning activity in lentic environments.…”
Section: Applying Edna or Erna To Test Ecological Or Biological Quest...mentioning
confidence: 99%